(untitled) (Quest Journal of Management and Social Sciences, 2020)
Background: Industry 4.0 is the revolution of industrial process along with the adaptation of technological changes and advancement. With the passage of time industry 4.0 has been catching the attention of industries all over the world. Various studies and literatures seem to be emerging regarding industry 4.0 around the globe. However, in Nepalese context no study has been conducted on the particular field. Objective:This study aims to study the current status of industries in Kathmandu valley and analyzes the factors affecting industrial readiness for industry 4.0 amidst the effects of the pandemic. It tries to review the industrial readiness for industry 4.0 in Nepal. Methods: Systematic literature review was conducted to analyze various literatures around the world along with 20 empirical reviews to make this study more efficient. Also, conceptual framework was developed to draw roadmap of the study. Results: We found that Nepal has got many problems in adoption of the concept of Industry 4.0. Our study noticed that along with the involvement of much unskilled labor force in industries, lack of infrastructural development and innovation, and ineffective government policy are the vital ones. Conclusion and implication: This study concludes that Nepal has huge unskilled workers relatively to skilled workers that are means for adaptation of new technologies, replacing manual work and the government from policy level needs to focus on this. This study will be beneficiary for Ministry of Information and technology, Ministry of industry, Ministry of Education, Health and science, Policy makers, Foreign as well as domestic investors, and for authors and graduating students in understanding industries readiness for 4.0 in Nepal.